GTP binding by Arabidopsis extra-large G protein 2 is not essential for its functions. Issue 2 (17th March 2021) - Maruta, Natsumi; Trusov, Yuri; Urano, Daisuke; Chakravorty, David; Assmann, Sarah M; Jones, Alan M; Botella, Jose R
Abstract: The extra-large guanosine-5′-triphosphate (GTP)-binding protein 2, XLG2, is an unconventional Gα subunit of the Arabidopsis ( Arabidopsis thaliana ) heterotrimeric GTP-binding protein complex with a major role in plant defense. In vitro biochemical analyses and molecular dynamic simulations show that affinity of XLG2 for GTP is two orders of magnitude lower than that of the conventional Gα, AtGPA1. Here we tested the physiological relevance of GTP binding by XLG2. We generated an XLG2(T476N) variant with abolished GTP binding, as confirmed by in vitro GTPγS binding assay. Yeast three-hybrid, bimolecular fluorescence complementation, and split firefly-luciferase complementation assays revealed that the nucleotide-depleted XLG2(T476N) retained wild-type XLG2-like interactions with the Gβγ dimer and defense-related receptor-like kinases. Both wild-type and nucleotide-depleted XLG2(T476N) restored the defense responses against Fusarium oxysporum and Pseudomonas syringae compromised in the xlg2 xlg3 double mutant. Additionally, XLG2(T476N) was fully functional restoring stomatal density, root growth, and sensitivity to NaCl, but failed to complement impaired germination and vernalization-induced flowering. We conclude that XLG2 is able to function in a GTP-independent manner and discuss its possible mechanisms of action. Abstract : Arabidopsis extra-large GTP-binding proteins have nucleotide-independent functions.